Enhanced Biosorption and Recovery of Copper and Zinc from Acetic Acid-Extracted Livestock Wastewater Sludge Using Baker’s Yeast - Jung-Jeng Su; Kuang-Wei Yen; Wei-Chen Chen (Animals)
This study aims to develop a novel use of baker’s yeast in biosorption as a sustainable metal recovery process for cost-effective and practical applications in recovering copper and zinc from waste gravity-thickened sludge generated at livestock wastewater treatment facilities. The supernatant of the acid-extracted product was separated from the residues through centrifugation. To ensure cost efficiency, the supernatant was treated with 2N acetic acid for 24 h, with the addition of hydrogen peroxide, and used for the biosorption experiments. The filtrated supernatant was adjusted to various pH values (4.5, 5.0, and 5.5) to explore the effects of acidity on the subsequent biosorption of extracted zinc and copper by baker’s yeast. A diluted molasses solution was added to the filtrate as a carbon source to support yeast growth during the 4 h biosorption experiments. The results revealed that the removal efficiency of zinc from the filtrate by baker’s yeast was 97.3%, while the removal efficiency for copper was about 48.8% at pH 5.5 with a reaction time of 4 h. In summary, this combined approach is expected to reduce and recycle heavy metals in livestock sludge. Acetic acid with hydrogen peroxide can extract copper and zinc from the sludge, and baker’s yeast can absorb both metals from the filtrate at pH 5.5 in a 4 h reaction time. This technological innovation has the potential to transform waste management practices in the livestock industry, contributing to resource recovery and environmental sustainability.